STRATEGI PEMBELAJARAN PAI DALAM MEMBENTUK SIKAP MODERASI BERAGAMA DI SEKOLAH MENENGAH PERTAMA: STUDI MULTISITUS - Mafruhatun Ni'mah; M.Muizzuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the strategies of Islamic Religious Education (PAI) learning in fostering religious moderation attitudes among junior high school students. Employing a qualitative approach with a multisite study design, the research was conducted at SMP Negeri 1 Turi and SMP Diniyah Al-Falahiyah Turi, which represent different educational contexts, namely a public school and a religion-based school. Data were collected through semi-structured interviews, classroom observations, and documentation, involving PAI teachers, school principals, and students.The findings indicate that PAI learning strategies in both schools are not merely oriented toward cognitive mastery of religious knowledge, but are also directed at shaping students’ moderate religious attitudes. At SMP Negeri 1 Turi, contextual and dialogical approaches are emphasized to address students’ diverse religious backgrounds. Meanwhile, SMP Diniyah Al-Falahiyah Turi integrates textual understanding of Islamic teachings with religious habituation, emphasizing a balance between religious commitment and openness to diversity. The process of internalizing religious moderation is supported by teacher exemplification, interactive learning practices, and school culture, although it is constrained by limited instructional time and the influence of simplistic religious content from digital media.This study concludes that effective PAI learning strategies play a significant role in fostering religious moderation when they are dialogical, contextual, and reflective. The findings contribute theoretically to the discourse on religious moderation as a pedagogical process and practically to the development of PAI learning strategies that are responsive to diverse educational contexts.